2015
DOI: 10.1007/s11882-014-0506-9
|View full text |Cite
|
Sign up to set email alerts
|

Interfaces Between Allergen Structure and Diagnosis: Know Your Epitopes

Abstract: Allergy diagnosis is based on the patient’s clinical history and can be strengthened by tests that confirm the origin of sensitization. In the past 25 years, these tests have evolved from the exclusive in vivo or in vitro use of allergen extracts, to complementary molecular-based diagnostics that rely on in vitro measurements of IgE reactivity to individual allergens. For this to occur, an increase in our understanding of the molecular structure of allergens, largely due to the development of technologies such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 92 publications
1
16
0
1
Order By: Relevance
“…13 Further study confirmed that about 18% of patients sensitized to B. tropicalis might have been caused by a cross-reaction. 20 In addition to dust mites, our study also found sensitization to cat/dog dander (31%), cockroach (27%), and pollen (24%). Mould might not have clinical significance since only a small number of patients were sensitized to it.…”
Section: Discussionsupporting
confidence: 50%
“…13 Further study confirmed that about 18% of patients sensitized to B. tropicalis might have been caused by a cross-reaction. 20 In addition to dust mites, our study also found sensitization to cat/dog dander (31%), cockroach (27%), and pollen (24%). Mould might not have clinical significance since only a small number of patients were sensitized to it.…”
Section: Discussionsupporting
confidence: 50%
“…They were possible thanks to peptide synthesis or to the development of recombinant technology, with in vitro expression of either allergen fragments, mutants, or allergen chimeras, and their subsequent testing for IgE antibody binding. The development of microarrays or bead-based epitope assays facilitated the investigation of the relevance of linear epitopes, using large sets of linear peptides ( 5 , 6 ). Microarrays have been especially useful for food allergens because they have mainly linear epitopes due to food processing and/or digestion ( 6 9 ).…”
Section: Historical Perspective To Ige Epitope Mappingmentioning
confidence: 99%
“…This might be a consequence of the hundred-fold increased cellular uptake of glycosylated proteins and peptides by antigen-presenting cells compared to their non-glycoslyated counterparts and resulting in enhanced immune responses [ 123 ]. However, others suggest that glycosylation is not a common critical determinant of allergenicity as food allergens comprise both glycoproteins as well as non-glycosylated proteins [ 124 ].…”
Section: Influence Of Maillard Reaction On Recognition Of Food Allmentioning
confidence: 99%